Zoledronic acid-induced mitochondrial impairment, inflammation, and oxidative stress in the rat kidney - Heresh Rezaei; Ayeh Rouhani; Jale Yüzügülen; Fatemeh Ghaderi; Rahil Fazlinezhad; Mohammad Reza Kiafar; Zahra Honarpishefard; Pargol Matinpour; Abdollah Arjmand; Negar Azarpira; Seyed Mohammad Amin Kashani; Forouzan Khodaei; et al. (Shiraz University of Medical Sciences, 2023)
Zoledronic acid (ZLD) is a bisphosphonate drug widely administered against pathological conditions such as hypercalcemia of malignancy, osteoporosis, bone metastases from solid tumors, and multiple myeloma. Unfortunately, renal injury is a serious and dose-limiting adverse effect of ZLD. There is no specific mechanism for ZLD-induced renal damage. The current study aimed to assess the effects of ZLD (10 and 15 mg/kg, i.p., single dose) on the rat kidney. In this regard, several parameters, including oxidative stress biomarkers, serum level of BUN and creatinine, inflammatory cytokines, kidney histopathology, and indices of mitochondrial function were assessed. A significant increase in serum Cr and BUN revealed renal injury. Moreover, kidney histopathological changes, including interstitial inflammation, tissue necrosis, and tubular atrophy, were detected in ZLD-treated rats. Biomarkers of oxidative stress, including a significant increase in reactive oxygen species (ROS), depletion of kidney glutathione (GSH) stores, increased lipid peroxidation, and suppression of the total antioxidant capacity, were detected in ZLD-treated animals. ZLD also significantly increased renal levels of TNF-α, IL-6, and IL-1β. ZLD exposure was also associated with significantly decreased mitochondrial dehydrogenases activity, mitochondrial depolarization, mitochondrial permeabilization, and ATP depletion. These data highlight mitochondrial dysfunction, inflammatory response, and oxidative stress as potential mechanisms in ZLD-induced kidney injury.